Analisis Perencanaan Pembelajaran Pendidikan Agama Islam Di SMPN 1 Kuala Pembuang - Rumsiti, Neneng (Syntax Idea, 2021)
In the field of Islamic Religious Education, planning is one of the important factors in educational activities in order to achieve the expected educational goals for each level and type of education at the national and local levels. The importance of good planning in the field of Islamic Religious Education because if there is no careful planning, the implementation of an activity will experience difficulties and even failure to achieve the desired goals. Therefore Islamic Religious Education as the best way of human life needs to be planned well and systematically. The hope is that Islamic Religious Education can truly penetrate the soul of every Muslim, especially school-age children. However, the application of Islamic Religious Education in general education institutions is a challenge in itself. This study aims to understand and analyze the Islamic Religious Education learning planning properly to achieve the goals of National education